2017
DOI: 10.1308/rcsann.2016.0297
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intramedullary nail breakage in proximal femoral fractures: a 10-year retrospective review

Abstract: INTRODUCTION Intramedullary nailing is a common treatment for proximal femoral fractures. Fracture of the nail is a rare but devastating complication that exposes often frail patients to complex revision surgery. We investigated which risk factors predict nail failure. METHODS We reviewed all cases of nail breakage seen over a 10-year period in a single busy trauma unit; 22 nail fractures were seen in 19 patients. Comparison was made with a group of 209 consecutive patients who underwent intramedullary fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 18 publications
2
53
0
Order By: Relevance
“…In regard to the types of proximal femoral fractures more commonly associated with IMN breakage, the findings that subtrochanteric and pathological fractures were more commonly associated with IMN breakage observed in the current study are also consistent with Johnson et al 15 A higher rate of IMN breakage in pathologic fractures was also observed by Willeumier et al 27 who found that 8% of patients with femoral metastases experienced breakage between 2000 and 2015 at five centers in the Netherlands. Only 7.4% of the fractures treated with IMN in the database were subtrochanteric and only 9% were pathological.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In regard to the types of proximal femoral fractures more commonly associated with IMN breakage, the findings that subtrochanteric and pathological fractures were more commonly associated with IMN breakage observed in the current study are also consistent with Johnson et al 15 A higher rate of IMN breakage in pathologic fractures was also observed by Willeumier et al 27 who found that 8% of patients with femoral metastases experienced breakage between 2000 and 2015 at five centers in the Netherlands. Only 7.4% of the fractures treated with IMN in the database were subtrochanteric and only 9% were pathological.…”
Section: Discussionsupporting
confidence: 91%
“…Closer follow-up of patient subgroups who may be at increased risk of IMN breakage and mechanical displacement of proximal femoral fractures might be beneficial until bony union has been achieved. 15 Johnson et al also suggest that other treatment options such as proximal femoral replacement may be considered for higher risk patients (eg, pathological fracture). 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johnson et al reported on 221 cases of 31 AO fractures with 22 nail breakages: 20 were Intramedullary Hip Screw® (IMHS) (Smith & Nephew™, Tennessee, USA) and 2 were Affixus® (AFF) (Zimmer Biomet™, Warsaw, Indiana, USA). All nails of this series were broken through the hole for the lag screw [ 26 ]. Therefore, there is no cephalomedullary nail reported in the literature not presenting the complication of nail breakage [ 13 – 16 ].…”
Section: Discussionmentioning
confidence: 99%